2013
DOI: 10.1603/en13081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Volatile and Nonvolatile Secondary Metabolites From Soybean Pods on Feeding and on Oviposition Behavior of <I>Euschistus heros</I> (Hemiptera: Heteroptera: Pentatomidae)

Abstract: Identification of chemical compounds extracted from host plants that act as oviposition stimulants for pest insects has gained importance, because of the compounds' potential use in the manipulation of insect behavior in the field. However, for generalist insects, such as phytophagous pentatomids, the chemical basis for the selection of the host is not well-known. Insect response can vary according to the soybean genotypes. Chemical profile of soybean pods of cultivars 'BRS 213', 'BRS 267', 'BR-16', and 'IAC-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…The differences in fecundity and the differential effect on the biological activity of Bt/Cry1Ac could be attributed to the differences in chemical composition of the washings. Plant surface chemicals have been reported to play an important role in insect oviposition (Chapman & Bernays, 1989;Green et al, 2003;Chamarthi et al, 2011;Hilker & Meiners, 2011;Silva et al, 2013). The present study suggested that surface chemicals play an important role in biological activity of Bt and/or Cry1Ac against H. armigera.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The differences in fecundity and the differential effect on the biological activity of Bt/Cry1Ac could be attributed to the differences in chemical composition of the washings. Plant surface chemicals have been reported to play an important role in insect oviposition (Chapman & Bernays, 1989;Green et al, 2003;Chamarthi et al, 2011;Hilker & Meiners, 2011;Silva et al, 2013). The present study suggested that surface chemicals play an important role in biological activity of Bt and/or Cry1Ac against H. armigera.…”
Section: Discussionsupporting
confidence: 54%
“…Chemicals on the surface of plant parts determine host acceptability and suitability of the host plant for development and survival of the insect pest (Chamarthi et al, 2011;Hilker & Meiners, 2011;Silva et al, 2013). Chemicals on the surface of plant parts determine host acceptability and suitability of the host plant for development and survival of the insect pest (Chamarthi et al, 2011;Hilker & Meiners, 2011;Silva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the flowering stage of a plant releases more volatile chemicals (Ceballos et al 2015) and provides nutritional rewards to many generalist herbivores than other stages (Wäckers et al 2007). However, the type of volatiles and their concentrations can vary between growth stages (Silva et al 2013). Such volatiles emitted by alyssum flowers could be extracted and artificially produced in a laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, flea beetles (Epitrix hirtipennis) were more abundant on GLVproducing wild type plants compared to plants (55). Uschistus heros preferred soybean pods that released high amounts of GLVs for feeding and oviposition over deficient cultivars (56). The GLVs serve as feeding stimulants to pests (57).…”
Section: Table1mentioning
confidence: 99%